Investigação da ação quelante e antioxidante da N-acetilcisteína sobre o cádmio - Caz, Priscila Da (2018)
Cadmium (Cd) is a heavy metal seen as an important pollutant for man. It is widely distributed in nature and also presents in cigarette and in production line of various industrial sectors. It has carcinogenic and toxic effects on organs such as brain, lung, kidney and liver due its excessive production of reactive oxygen species (ROS). N-acetylcysteine (NAC) is a mucolytic agent that exhibits properties as antioxidant and chelating agent due its ability to reduce reactive oxygen species and provide chelating sites for metals. Therefore, NAC is effective in detoxification process. This study has validated a method for cadmium quantification in plasma of rats by atomic absorption spectrometry with electrothermal atomization in graphite furnace (GFAAS). It presented satisfactory and approved results. The protective action of NAC on lipid peroxidation in renal tissue of rats submitted to cadmium intoxication was also investigated. The results showed that NAC presents protective effect to reverse lipid peroxidation suggesting that it preserves renal tissue damage caused by cadmium.